Effective and sustainable Cs+ remediation via exchangeable sodium-ion sites in graphene oxide fibers (vol 7, pg 17754, 2019) - Lee, Heehyeon; Lee, Kyungeun; Kim, Sang Ouk; Lee, Jae-Seung; Oh, Youngtak (Royal Society of Chemistry, 2019)
Correction for 'Effective and sustainable Cs+ remediation via exchangeable sodium-ion sites in graphene oxide fibers' by Heehyeon Lee et al., J. Mater. Chem. A, 2019, 7, 17754-17760.